Piezoelectric behaviour of PZT doped with calcium: A combined experimental and theoretical study - Cerqueira, M.; Nasar, R. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Beltran, A.; Llusar, R.; Andres, J. (Chapman Hall Ltd, 1997)
An experimental and theoretical study on the piezoelectric behaviour of PZT doped with a range of calcium ion concentrations is presented. A systematic study of the effect on the piezoelectric properties of PZT doped with various concentrations of CaO at constant sintering temperature and sintering time was carried out. The remanent polarization, planar coupling factor and frequency-thickness constant increase with calcium concentration. Ab initio perturbed ion calculations show that the lattice energy decreases with calcium addition for both tetragonal and rhombohedral phases of PZT.